2016
DOI: 10.1071/an15519
|View full text |Cite
|
Sign up to set email alerts
|

A novel and effective technology for mitigating nitrous oxide emissions from land-applied manures

Abstract: Abstract. Land-applied manures produce nitrous oxide (N 2 O), a greenhouse gas (GHG). Land application can also result in ammonia (NH 3 ) volatilisation, leading to indirect N 2 O emissions. Here, we summarise a glasshouse investigation into the potential for vermiculite, a clay with a high cation exchange capacity, to decrease N 2 O emissions from livestock manures (beef, pig, broiler, layer), as well as urea, applied to soils. Our hypothesis is that clays adsorb ammonium, thereby suppressing NH 3 volatilisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Biochar and bentonite most strongly reduced the soil concentration of extractable inorganic N. Testing these sorbents in the laboratory, we confirmed that both effectively sorb NH 4 + [30,31]. In the present study, sorbents were mixed with the N source immediately prior to application to the soil, which may explain why our findings differ from previous studies where pre-incubation resulted in over~50% greater NH 4 + sorption (e.g., [46,53]). Because water and solutes diffuse slowly in bentonite [54], and possibly biochar, pre-incubating sorbents with N-rich materials could attenuate the early release of inorganic N. For the development of nextgeneration fertilisers based on organic wastes and sorbents, pre-incubation should therefore be considered.…”
Section: Emissions Of N2o and Other Greenhouse Gases From The Field Experimentssupporting
confidence: 61%
See 1 more Smart Citation
“…Biochar and bentonite most strongly reduced the soil concentration of extractable inorganic N. Testing these sorbents in the laboratory, we confirmed that both effectively sorb NH 4 + [30,31]. In the present study, sorbents were mixed with the N source immediately prior to application to the soil, which may explain why our findings differ from previous studies where pre-incubation resulted in over~50% greater NH 4 + sorption (e.g., [46,53]). Because water and solutes diffuse slowly in bentonite [54], and possibly biochar, pre-incubating sorbents with N-rich materials could attenuate the early release of inorganic N. For the development of nextgeneration fertilisers based on organic wastes and sorbents, pre-incubation should therefore be considered.…”
Section: Emissions Of N2o and Other Greenhouse Gases From The Field Experimentssupporting
confidence: 61%
“…Amendments were thoroughly mixed with the manure before being applied to soil. In previous research, manure-sorbent blends were incubated for over a week to maximise the contact of N ions and sorbent [45,46]. Here, treatments were applied within 1 h of mixing so that we could determine if rapidly assembled treatments are effective at the field-scale.…”
Section: Experimental Designmentioning
confidence: 99%
“…The N 2 O emission decrease was attributed to NH 4 + exchange on the negatively-charged zeolite and subsequent nitrification suppression [142]. Hill et al [143] investigated the potential for vermiculite-a high cation exchange capacity clay-to decrease N 2 O emissions from organic and chemical N fertilisers applied to a range of soils in a glasshouse trial. These authors reported an average 70% decrease in N 2 O emissions at a vermiculite application rate of 7 t/ha over a one-year period.…”
Section: Nitrous Oxidementioning
confidence: 99%
“…In addition to promoting methanotroph growth and activity via physical processes, as alluded to by Brandt, et al 104 , the expanded vermiculite may have helped maintain sufficient nitrogen concentrations for microbial activity via ammonium sorption. Previous work by Hill, et al 115 and Pratt, et al 116 has shown that vermiculite, which is a high cation-exchange capacity clay, can effectively bind soil and solution ammonium through exchange processes. It might be possible to overcome nutrient deficiency to methanotrophs through other sustainable approaches, such as incorporating nitrogen-fixing bacterial strains into the filter or by trickling nutrient-rich waste streams over the filter in applications relating to agriculture, landfills and wastewater treatment.…”
Section: Engineered Biofilters -Novel Design Approaches and Applicationsmentioning
confidence: 99%